Two new species of Dendrobium (Orchidaceae: Epidendroideae) from China: evidence from morphology and DNA - Xu, Qing; Zhang, Guo-Qiang; Liu, Zhong-Jian; Luo, Yi-Bo (Phytotaxa, 2014)
Two new orchid species, Dendrobium wenshanense and D. longlingense, from Yunnan, China, are described and illustrated in this study based on morphological and molecular evidence. Morphological analysis indicates that D. wenshanense is similar to D. wilsonii and D. fanjingshanense, but they differ in floral color, length of column foot and shapes/sizes of sepals, petals and lip; D. longlingense is similar to D. longicornu, but differs in presence of black hairs on adaxial surface of leaf, position of inflorescences, floral color and shapes of lip and spur. Molecular analysis of combined nuclear and plastid datasets (ITS, matK, rbcL, trnH-psbA, trnL intron) reveals that D. wenshanense is sister to D. wilsonii and D. fanjingshanense and a member of section Dendrobium; D. longlingense is sister to D. longicornu and a member of section Formosae.